Tagging web images for blind users. - Misman, Ahmad Fatzilah; Blanchfield, Peter (IIUM Press, 2011)
One way to remedy the gap that evidently exists between the image element on the web and the web user who is visually blind is by redefining connection between the image and the abundant element of the web itself i.e. text. Studies on the web image automatic descriptors are largely done from the perspective of the fields of the He!. the semantic web. the information retrieval or a hybrid approach. This paper however suggests that a solution is possible by adapting the web images resources considering the factors for web image's being used in developer's and blind user's perspectives. An effective and appropriate auto image tagger may consider this v